Crystal alignment of caffeine deposited onto single crystal surfaces via hot-wall epitaxy12. Issue 21 (17th May 2017) - Röthel, Christian; Radziown, Michal; Resel, Roland; Grois, Andreas; Simbrunner, Clemens; Werzer, Oliver
Abstract : Crystal growth of caffeine on single crystalline surfaces yields needle or bird-like shaped crystals depending on surface chemistry and symmetry. Abstract : Defined crystal growth is highly demanded for technological applications but also fundamental research. Within this work, the crystal growth of the asymmetric molecule caffeine was studied on single crystalline surfaces of muscovite mica, sodium chloride and potassium chloride. While elongated needle-like crystals grow on muscovite mica and sodium chloride, smaller individual "bird-like" structures were observed on potassium chloride. Depending on the surface type and temperature, the disk-shaped caffeine molecules prefer either an edge-on or flat-on orientation with respect to the surface, but in each case, a defined crystallographic relation between the surface and caffeine crystallites was determined by using the X-ray pole figure technique. On muscovite mica and sodium chloride, needle-like crystallites with edge-on oriented molecules aligned mainly with the unit cell c -axis (which coincides with the long needle axis) along the [1−10]mica, [100]mica, [110]mica and [110]NaCl, [1−10]NaCl directions, respectively. Crystals consisting of flat-on oriented molecules on KCl showed also defined alignments with respect to the substrate, but due to the altered molecule–substrate contact, the b -axis aligned along [110]KCl and [1−10]KCl . Growth at elevated temperatures enabled changes in the crystal growth whereby more defined structures formed on NaCl. On KCl, the bird-like structures remained very similar, while caffeine on the mica surface at elevated temperatures resulted in even additional texture forming with the caffeine molecules now also favoring a flat-on orientation with respect to the surface. The systematic variation of various system parameters demonstrates how sensitive the growth behavior of caffeine on this variety of substrates is.